Drug utilization research in Peru: Is real-world data available? - Rodríguez-Tanta, L. Yesenia; Garavito Farro, Héctor; Freitas Leal, Lisiane; Salas, Maribel; Elseviers, Monique M.; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2023)
Drug utilization research (DUR) is used to provide evidence-based data to inform policies and make decisions. The aim of this study was to map and describe available data sources for DUR in Peru. We performed a search of data sources providing information on medication use on the website of governmental organizations. We also conducted a literature review using PubMed, LILACs, and BVS. Independently, researchers screened eligible data sources. Data characterization included accessibility, coverage data provider, type of data sources, and setting. We performed a descriptive analysis. We identified seven data sources, VIGIFLOW, ENSUSALUD, ICI, and IDI (SISMED) from MINSA and CRI-ESSALUD, Central Planning and Budget Management, and Hospital Management from ESSALUD. These presented information on adverse drug reactions (n=2), drug consumption, and distribution (n=2), prescription and drug dispensing (n=1), and surveys addressed to medication users (n=2). ENSUSALUD was the only data source publicly available. VIGIFLOW and ENSUSALUD have a national granularity from the public and private sectors. The setting of the data sources was both hospital and ambulatory care. Two data sources have individual-level data on adverse drug reactions and one on prescriptions. Four studies on drug utilization research in Peru were derived from ENSUSALUD. In Peru, few data sources are available for DUR. There is an increased need to monitor medications for decision-making purposes. Local and international initiatives and partnerships of the government with academic institutions and the private sector might be a good strategy to increase the transparency of health data and for supporting decision-making using DUR.